PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN MENGGUNAKAN METODE KOOPERATIF TIPE THINK PAIR SHARE (BERPIKIR, BERPASANGAN, DAN BERBAGI) PADA SISWA KELAS VII SMP NEGERI 4 BULUKUMBA - Sakinah Fitri (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
Abstract. Upgrades Writing Poetry with Type Cooperative Method Using Think Pair Share to the Seventh Grade Students of SMP Negeri 4 Bulukumba. This study aimed to describe the planning, implementation, and assessment of learning to write poetry using cooperative Think Pair Share (Think, in pairs, and Share) at class VII SMP Negeri 4 Bulukumba. This study includes qualitative descriptive study was designed through action research class (class room action research). The research was conducted in class VII SMP Negeri 4 Bulukumba. The research data is in the form of action response behavior of teachers and students in the learning interactions writing poems in class. Source of research data is the data of teachers and students of class VII SMP Negeri 4 Bulukumba by the number of students 27 people. The instruments used are observation, interview and test. This research data analysis technique is descriptive technique. The results of this study indicate that the acquisition value of students using cooperative strategies SMT type also increasing, with the average value of students in the first cycle was 75.22 increased in the second cycle into 82.85. Another indicator of the increase can be observed based on the learning outcomes of the first cycle and the second cycle to the changes, especially in changing attitudes and values of students in learning.